Changes in DNA Methylation in Arabidopsis thaliana Plants Exposed Over Multiple Generations to Gamma Radiation - Laanen, Pol; Saenen, Eline; Mysara, Mohamed; Van de Walle, Jorden; Van Hees, May; Nauts, Robin; Van Nieuwerburgh, Filip; Voorspoels, Stefan; Jacobs, Griet; Cuypers, Ann; Horemans, Nele (Frontiers in Plant Science, 2021)
Previous studies have found indications that exposure to ionising radiation (IR) results in DNA methylation changes in plants. However, this phenomenon is yet to be studied across multiple generations. Furthermore, the exact role of these changes in the IR-induced plant response is still far from understood. A multigenerational set-up was used in which three generations of seven-day old Arabidopsis thaliana plants were exposed to either of the different radiation treatments (30 mGy/h, 60 mGy/h, 110 mGy/h, or 430 mGy/h) or to natural background radiation (control condition) for 14 days. The parental generation consisted of previously non-exposed plants, whereas first and second generation plants had already received a similar irradiation in the previous one or two generations, respectively. Next to whole genome methylation levels, differentially methylated regions (DMRs), including their methylation context in the three generations a were identified. Both intra- and intergenerational comparisons of the genes and transposable elements associated with the DMRs were made. Taking the methylation context into account, the highest number of changes were found for cytosines followed directly by guanine (CG methylation), whereas only limited changes in CHG methylation occurred and no changes in CHH methylation were observed. A clear increase in IR-induced DMRs was seen over the three generations that were exposed to the lowest dose rate, where generation 2 had a markedly higher number of DMRs than the previous two generations (Parent and generation 1). No significant differences in the plants exposed to the highest dose rate were found. A large number of DMRs associated with transposable elements were found, the majority of them being hypermethylated, likely leading to more genetic stability. Next to that, a significant number of DMRs were associated with promoter-associated regions or gene bodies. A functional analysis of these genes showed an enrichment for genes related to development as well as various stress responses, including DNA repair, RNA splicing, and (a)biotic stress responses. These observations indicate a role of DNA methylation in the regulation of these genes in response to IR exposure and shows a possible role for epigenetics in plant adaptation to IR over multiple generations.